Supervision Stage: an experiment in teachers training - Rocha, Karla Marques da (2014)
This paper discusses the use of Web-based Educational Technologies, specially the Wiki activity tool in Moodle, on the subject of Supervised Teacher Training of the Special Undergraduate Program of Teachers’ Education for Professional and Technological Education of UFSM. The posts made by 29 students and their advisor were analyzed with regards to their teaching lessons and their implementation. The posts enabled a discussion on the Wiki space fostering categories of indicative elements for the supervision for future training by means of conversation networks. The possibility of follow-up, guiding, evaluations and learning became effectively a period of constructing experiences, beyond the academic space.